ANATOMICAL STRUCTURE AND MORPHOMETRY OF THE LUNGS OF BALI DUCKS IN THE GROWER PHASE - Kimberley Felicia Putri; Ni Luh Eka Setiasih; Ni Nyoman Werdi Susari; I Ketut Berata; Luh Gde Sri Surya Heryani; I Ketut Suatha (Buletin Veteriner Udayana, 2024)
The lungs are an organ that functions as a place for air exchange, where the incoming air will be used for combustion and energy production. Poultry lungs contain three main elements, namely primary bronchi, secondary bronchi and parabronchi. This study aims to determine the structure and morphometry of new lungs of bali ducks (Anas sp.) of different sexes in the growing phase. This research used 18 balinese ducks which were divided into 2 groups, namely male and female with 9 each (three months old). Anatomical structure examination was carried out by direct observation and histological structure using a binocular light microscope. The results of the anatomical and histological structure data were analyzed using descriptive qualitative analysis, while the morphometric data were analyzed using the Independent Sample T-Test. The anatomical structure of the bali duck's lungs is trapezoidal with conical ends, firmly attached to the thorax, stiff and pink in color, consisting of primary bronchi, secondary bronchi and many parabronchi. The parabronchi consist of the parabronchial wall, parabronchial lumen, septa, arteries/veins, atria, blood capillaries and air sacs. The results of lung morphometry measurements of bali ducks showed that there were no significant differences (P>0.05) in weight, volume, length and width. The results of histomorphometric measurements on the area of the parabronchi, thickness of the parabronchi walls and septa showed significant differences (P<0.05) in the two sexes. There is no difference in the anatomical structure and histology of the lungs of male and female Bali ducks, but there are differences in morphometry. There is no difference in the anatomical structure of the lungs between male and female balinese ducks in the grower phase, no difference in macro morphometry, but in histomorphometric examination there are differences in parabronchial area and septa width, there is no difference in the thickness of the parabronchial walls of male and female Balinese ducks in the grower phase.female Bali ducks are the same, but there are differences in morphometry.